1988
DOI: 10.1103/physrevlett.61.1871
|View full text |Cite
|
Sign up to set email alerts
|

Photostimulated desorption in laser-assisted etching of silicon

Abstract: Photodesorption of SiF3 groups, which are the principal adsorbates on a silicon surface during etching by XeF2, is found to be responsible for the etch-rate enhancement observed under illumination by lowpower, cw band-gap radiation. It is proposed that desorption is stimulated by a photogenerated-chargecarrier-mediated chemical reaction, and not the simple charge trapping and recombination mechanism usually invoked for desorption from semiconductor surfaces. 73.25.+i, 82.65.My When surface reactions produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Nanoscale silicon can be obtained using numerous techniques, including solution synthesis 17 , spark discharge 18 , laser-stimulated etching 19,20 , plasma synthesis 21,22 or ball milling 23 . The application of different production approaches results in different physical and chemical properties of the final materials 24 , in particular, crystallinity, contamination with metal ions, surface oxidation and particle-size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoscale silicon can be obtained using numerous techniques, including solution synthesis 17 , spark discharge 18 , laser-stimulated etching 19,20 , plasma synthesis 21,22 or ball milling 23 . The application of different production approaches results in different physical and chemical properties of the final materials 24 , in particular, crystallinity, contamination with metal ions, surface oxidation and particle-size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…2͑b͒, the exposed second layer accounts for 52% of the surface. The incremental removal associated with those 1.8ϫ10 4 laser shots was 0.27 ML and the emission yield was 1.3ϫ10 10 atoms/cm 2 per pulse ͑hϭ2.3 eV, pulse fluence 35 mJ cm Ϫ2 ͒. Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Several studies of laser-enhanced etching have shown the importance of electronic excitations of the reactant/surface ensemble, in which photocarriers participate directly in the reaction. [1][2][3][4][5] In addition, relaxation and recombination of these photocarriers lead to a surface temperature rise and possibly thermally activated etching. 1,2 The relative importance of these two components, photocarrier-induced etching and laser heating, depends on the intensity and wavelength of the laser as well as the optoelectronic and thermal properties of the system under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Lithography and chemical etching are powerful methods that can control the shape and size of formed micro‐ and nanostructures, but they are usually complex and costly . In contrast, pulsed laser irradiation on the substrate of different materials also can observe a variety of micrometer‐scale and nanometer‐scale structures . It is a simple but effective method for fabricating small structures directly onto a substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In contrast, pulsed laser irradiation on the substrate of different materials also can observe a variety of micrometer-scale and nanometer-scale structures. [2][3][4][5][6][7][8][9][10][11] It is a simple but effective method for fabricating small structures directly onto a substrate. This can offer the local modification of solid-state devices, where the advantages of onestep, mask-free processing may have more important value than lithographic techniques.…”
Section: Introductionmentioning
confidence: 99%